Job quality and internal migration in Colombia in 2015 - Castillo Aroca, Alberto (2018)
In the current study a Composite Index of Employment Quality (CIEQ) was calculated for the departments of Colombia, distinguishing between urban and rural areas. For this purpose, data from the, Great Integrated Survey of Households (GEIH) for the years 2014 and 2015 was used. Subsequently, regression models for binary outcomes (logit and probit) were used to determine how the sub-indexes concerning to the dimensions of the CIEQ explain the decision to migrate from the EAP of Colombia across the country.